2021
DOI: 10.1371/journal.pone.0253576
|View full text |Cite
|
Sign up to set email alerts
|

The protective association between statins use and adverse outcomes among COVID-19 patients: A systematic review and meta-analysis

Abstract: Introduction Statins may reduce a cytokine storm, which has been hypothesized as a possible mechanism of severe COVID-19 pneumonia. The aim of this study was to conduct a systematic review and meta-analysis to report on adverse outcomes among COVID-19 patients by statin usage. Methods Literatures were searched from January 2019 to December 2020 to identify studies that reported the association between statin usage and adverse outcomes, including mortality, ICU admissions, and mechanical ventilation. Studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
4
22
0
5
Order By: Relevance
“…The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…The adherence issue observed during lockdown may lead to worse cardiometabolic disease outcomes. Of note, among patients with COVID-19, statin use is a proxy of comorbidities that expose patients to more severe COVID-19 [60], although statin users seem to have a better COVID-19 clinical course than non-statin users [61]. The postulated mechanisms to explain this finding include direct cholesterol-lowering effects on viral infection/replication and several statin pleiotropic effects [62] due to their antithrombotic, anti-inflammatory, and immunomodulatory properties [63].…”
Section: Working From Home and Cardiometabolic Diseasementioning
confidence: 99%
“… 18 , 19 Similarly, a recent systematic review and meta-analysis including 110 078 hospitalized COVID-19 patients across thirteen retrospective cohorts found statin administration after diagnosis was associated with decreased mortality, particularly among individuals not requiring intensive care. 20 In contrast to the current study, which found a reduced risk of COVID-19 infection but not severity, observational studies have largely focused on the effects of statin treatment on COVID-19 outcomes rather than infection. The current MR study thus complements the published literature, which in sum suggests that therapies modifying circulating cholesterol and ApoB levels may have beneficial effects on COVID-19 infection and severity.…”
mentioning
confidence: 69%